Patients’ Experiences of Participating Actively in Shared Decision-Making in Mental Care - Lise Sæstad Beyene PhD(c); Elisabeth Severinsson DrPH; Britt Sætre Hansen PhD; Kristine Rørtveit PhD (Journal of Patient Experience, 2019)
Background: Patients in mental care express a wish for more active participation. Shared decision-making is a way of increasing patient participation. There is lack of research into what the shared decision-making process means and how the patients can participate in and experience it in the context of mental care. Objective: To describe patient participation in shared decision-making in the context of indoor mental care. Method: A qualitative content analysis of data from in-depth interviews with 16 patients was performed. Results: One main theme was revealed: thriving in relation to participating actively in a complementary ensemble of care , which represented the red thread between 2 themes: having mental space to discover my way forward and being in a position to express my case . Conclusion: Patients can participate actively in shared decision-making when the patients’ and the mental health-care professionals’ joint expertise is applied throughout their mental care. The patients experience thriving when participating actively in a complementary ensemble of care.